Clinical Features and Gene Mutation Analysis of Congenital Thrombotic Thrombocytopenic Purpura in Neonates - Wang, Jiali; Zhao, Li (Frontiers in Pediatrics, 2020)
Background: To analyze the clinical characteristics of congenital thrombotic thrombocytopenic purpura (TTP) in neonates and the mutation sites of ADAMTS13 gene encoding vWF lyase. Case presentation: The clinical characteristics of a newborn suspected with TTP were analyzed. A high throughput sequencing technique was used to screen genes related to genetic metabolic diseases. The mutations of ADAMTS13 in blood samples of the newborn and its parents were detected using polymerase chain reaction (PCR) and Sanger sequencing. Besides, we compared the clinical characteristics and mutation sites of ADAMTS13 with other TTP newborns by retrieving literature involved in China National Knowledge Infrastructure (CNKI), Wanfang database and Pubmed. Conclusion: This case enriches the clinical manifestations and gene mutations of neonatal TTP. High throughput sequencing technology can be applied to gene testing of suspected TTP children. The mutation of c.1187G > A and c.1595G > T in ADAMTS13 are novel missense mutations in neonatal TTP, which has not been reported worldwide.